2007
DOI: 10.2193/2005-554
|View full text |Cite
|
Sign up to set email alerts
|

American Woodcock Fall Migration Using Central Region Band‐Recovery and Wing‐Collection Survey Data

Abstract: Band‐recovery and wing‐collection survey data have the potential to provide information on American woodcock (Scolopax minor) fall migration ecology in the Central Region of the United States, yet researchers have not recently analyzed these extensive data sets. We analyzed all direct recoveries of woodcock banded in Michigan, Minnesota, and Wisconsin, USA, as well as wing‐collection survey data, to determine the progression of fall migration, the migration direction, and the final destination of woodcock migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…Some woodcock arrive on wintering grounds in October, whereas winter abundances usually peak in mid‐December (Roberts ) and the northern limit of wintering habitat is variable among and within years (Roberts ), suggesting that woodcock use a range of fall migration strategies. Mixing during migration or winter may confound the north‐to‐south progression of autumn departure based on latitude (Myatt and Krementz , Meunier et al ) and would explain why the linear regression of encounter and banding location latitude of 341 pre‐season‐banded and winter‐encountered juvenile woodcock does not provide evidence of a leapfrog migration strategy. Furthermore, limited departure data and band recoveries (only ∼200 recovered from 1939 to 2010) from Canada make it difficult to examine migration strategies used by woodcock in the most northerly portions of their range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some woodcock arrive on wintering grounds in October, whereas winter abundances usually peak in mid‐December (Roberts ) and the northern limit of wintering habitat is variable among and within years (Roberts ), suggesting that woodcock use a range of fall migration strategies. Mixing during migration or winter may confound the north‐to‐south progression of autumn departure based on latitude (Myatt and Krementz , Meunier et al ) and would explain why the linear regression of encounter and banding location latitude of 341 pre‐season‐banded and winter‐encountered juvenile woodcock does not provide evidence of a leapfrog migration strategy. Furthermore, limited departure data and band recoveries (only ∼200 recovered from 1939 to 2010) from Canada make it difficult to examine migration strategies used by woodcock in the most northerly portions of their range.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals with natal origins in mid‐latitudes would exhibit a more facultative migration strategy within the migration continuum by traveling cumulatively shorter distances between natal and winter locales. Conversely, woodcocks with natal origins in the northernmost portions of the breeding range would exhibit a longer distance, more obligate leapfrog migration, in which those individuals would winter in the southernmost regions of their winter range (Myatt and Krementz ). The latter phenomenon is not unprecedented in other shorebirds, and has been frequently documented (Boland , Piersma et al , Johnson et al , Minias et al , Duijns et al ).…”
mentioning
confidence: 99%
“…Woodcock initiate fall migration in the Central Region in late October and early November (Keppie andWhiting 1994, Myatt andKrementz 2007). The northern extent of winter distribution of woodcock has been reported from northern Louisiana (Owen 1977) to as far north as Missouri, USA (Straw et al 1994).…”
mentioning
confidence: 99%
“…Myatt and Krementz ). Finally, Myatt and Krementz () tracked autumn migrating radio‐marked woodcock from Minnesota, Wisconsin, and Michigan and found that of 33 marked woodcock located, only a single bird of was found in the lower Mississippi Alluvial Valley. Based on their findings, Myatt and Krementz () proposed that woodcock avoid the lower Mississippi Alluvial Valley and instead migrate around it along the bluffs of the Valley (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2 Myatt and Krementz 2007b). Finally, Myatt and Krementz (2007a) tracked autumn migrating radio-marked woodcock from Minnesota, Wisconsin, and Michigan and found that of 33 marked woodcock located, only a single bird of was found in the lower Mississippi Alluvial Valley.…”
Section: Discussionmentioning
confidence: 99%